Clarifying the PSA grey zone: The management of patients with a borderline PSA. Issue 11 (27th September 2016) - Ross, Talisa; Ahmed, Kamran; Raison, Nicholas; Challacombe, Ben; Dasgupta, Prokar
Summary: Introduction: Prostate specific antigen is a marker for prostate cancer and a key diagnostic tool, yet when to refer patients with a borderline PSA is currently unclear. This review describes how to assess a patient with borderline PSA and provides an algorithm for management. Methods: Current literature on reference values, factors affecting PSA, indications for referral, non‐invasive investigations and the role of MRI were reviewed. Medline and EMBASE were searched using MeSH terms. Results: The literature suggests that a PSA of over 1.5 ng/mL should be used as a cut‐off to consider further testing for all age groups. There is strong evidence to show that adjuncts are useful when interpreting PSA results, most notably percentage free PSA and proPSA. Considerable weighting should also be given to the ERSPC risk calculator when deciding when to refer. Multi‐parametric MRI is valuable in closely examining suspicious lesions to reduce the number of negative biopsies. MRI fusion biopsy (TRUS, transrectal ultrasonography or transperineal) should be considered over standard TRUS biopsy to detect more clinically significant disease. Conclusions: Management of borderline PSA is not straightforward. A cut‐off of 1.5 ng/mL should be used in conjunction with digital rectal exam, risk calculation and PSA adjuncts. Imaging and biopsy should utilise mpMRI to achieve improved diagnosis of clinically significant prostate cancer, with fewer unnecessary investigations.